AB0742 Hand x-ray lesions are frequent in antisynthetase syndrome patients with arthralgia and increase with the radiographic follow-up, whatever the extra-articular features and the serotype of antisynthetase syndrome. (12th June 2018) - Guillochon-Petitcuenot, C.; Bierry, G.; Maurier, F.; Afif, N.; Messer, L.; Gottenberg, J.-E.; Sibilia, J.; Meyer, A.
Abstract : Background: Arthritis is frequent in antisynthetase syndrome (ASS) but the prevalence, the characteristics and the risk factors of radiographic lesions have been poorly assessed. Objectives: To report prevalence, characteristics and risk factors of radiographic abnormalities in ASS patients with arthralgia. Methods: A mono-centric cohort of 101 patients with ASS and arthralgia was screened for hand X-ray availability. Patients with osteoarthritic lesions were excluded from the analysis. ASS patients with radiographic lesions were compared to ASS patients with normal X-ray. Results: Thirty one patients were included. Thirteen patients (41.9%) had radiographic lesions on hand X-ray, including periarticular calcifications (53.8%), joint pinching (46.1%), erosions (23%), and subluxations (15.3%). Age (54.15±4.5 vs 49.17±3.3 years old, p=0.17) and sex ratio were similar in both groups. Duration of ASS was two-fold longer at first hand X-ray with radiographic lesion compared to the ASS patient without radiographic lesion at last radiographic follow-up (10, 08±2, 4 years vs. 4, 83±1, 6, p=0, 06). However, the cumulative number of immunomodulatory drugs at first hand X-ray with radiographic lesion or last hand X-ray if normal tended to be lower in patients with radiographic lesions (0, 818 vs 1, 28, p=0, 55). History of extra-articular involvements (including myositis, interstitial lung disease, skin lesions and Raynaud phenomenon) were not different in both groups, although mechanic's hand tended to be less frequent in patients with radiographic lesions (23.1% vs 61.1%, p=0.07). Patients with radiographic lesions had more frequently anti-EJ (31% vs. 0%, p<0.05). Other anti-tRNA synthetase antibodies were not significantly associated with abnormal hand x-ray which were found in 50% of anti-PL-7 positive patients (2/4), 33, 3% of anti-PL-12 positive patients (1/3), 30% of anti-Jo1 positive patients (6/20), and 0/1 anti-OJ positive patient (one patient was positive for anti-Jo1 and anti-PL7). ACPA (27.3% vs 7.1%, p=0.29) and rheumatoid factor (50% vs 14.2%, p=0.09) were more frequently positive in case of radiological abnormality. Conclusions: Hand X-ray lesions are frequent in ASS patients with arthralgia, whatever the extra-articular features and the ASS serotype and was associated is a longer duration of ASS. Disclosure of Interest: None declared